Perkembangan dan implementasi perizinan usaha berbasis Online Single Submission terhadap Usaha Mikro Kecil dan Menengah - Putri, Febi Ananda (Maliki Interdisciplinary Journal, 2023)
In making business licenses, business owners must go through a long and complicated bureaucratic process because the service is still manual-based and there are many files that must be prepared and requirements that must be met, business actors also have to incur costs during the permit application process to prepare files and also transportation costs. Along with the development of the digital-based era, licensing has also experienced a revolutionary evolution with the holding of an electronic licensing system to facilitate licensing. Therefore this study aims to find out more about the development of MSMEs and Online Single Submission (OSS) business licensing in Indonesia and to find out the implementation of Online Single Submission (OSS) based business licensing for MSMEs in Indonesia. In answering these objectives this research uses normative juridical research methods. By using normative juridical research methods, it can be concluded that the development of MSMEs in Indonesia is quite good and still has good prospects for improvement. Meanwhile, the implementation of OSS is still considered ineffective and inefficient. This can be proven by the existence of various kinds of obstacles. In the implementation of OSS there are also supporting and inhibiting factors.